Fluid balance of elite female basketball players before and during game play - Brandenburg, J. P.; Gaetz, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
This study determined the fluid balance of elite female basketball players before and during competition. Before and during 2 international games, 17 national-level players (age 24.2 ± 3 yr, height 180.5 ± 6 cm, mass 78.8 ± 8 kg) were assessed. Fluid-balance assessment included pregame hydration level as determined by urine specific gravity (USG), change in body mass during the game, ad libitum intake of water or sports drink, and estimated sweat losses. Mean (± SD) USG before Game 1 was 1.005 ± 0.002 and before Game 2 USG equaled 1.010 ± 0.005. Players lost an average of 0.7% ± 0.8% and 0.6% ± 0.6% of their body mass during Games 1 and 2, respectively. In each game, 3 players experienced a fluid deficit >1% of body mass, and 1 other, a fluid deficit >2%. Sweat losses in both games, from the beginning of the warm-up to the conclusion of the game (~125 min with average playing time 16-17 min), were approximately 1.99 ± 0.75 L. Fluid intake in Game 1 and Game 2 equaled 77.8% ± 32% and 78.0% ± 21% of sweat losses, respectively. Most players were hydrated before each game and did not become meaningfully dehydrated during the game. It is possible that the players who experienced the highest levels of dehydration also experienced some degree of playing impairment, and the negative relationship between change in body mass and shooting percentage in Game 2 provides some support for this notion.